Oceanographic Buoys for Marine Monitoring: A Review of Instrumentation, Applications, and Emerging Technologies - Francisco Portillo; Nadia Rotbi; Nicolas Padilla; Consolacion Gil; John Alexander Taborda; Alfredo Alcayde; Maria Isabel Saez (Journal of Marine Science and Engineering, 2026)
Oceanographic buoys are essential platforms for marine observation, supporting real-time monitoring, climate studies, operational oceanography, coastal management, and offshore activities. This review maps the scientific literature on oceanographic buoys and identifies the main research sectors that structure the field. A Scopus search using TITLE-ABS-KEY((oceanographic OR metocean OR “ocean observing” OR “ocean observation”) AND (buoy OR buoys)) retrieved 1876 documents published between 1938 and 2026. The records were processed using a network-based sector detection and visualization workflow. Five thematic sectors were identified: platform engineering, sensors, moorings, and autonomous systems; marine wind, waves, metocean, and offshore energy applications; physical oceanography, sea-surface temperature (SST), currents, and environmental variability; coastal and ocean observing networks and operational services; and drifting buoys, floats, and global ocean datasets. The results show that buoy research has evolved from isolated measurement systems to integrated observing infrastructures that combine in situ sensing, satellite validation, autonomous operation, telemetry, and decision-support services. By linking bibliometric structure and thematic interpretation, this review provides a sector-based map showing where scientific observation, engineering design, operational services, and autonomous technologies converge.

The threat of multidrug-resistant microorganisms: active surveillance of key antimicrobial resistant pathogens in 2025 - a report from the INVIFAR network - Adrián Martínez-Meléndez; Elvira Garza-González; María del Rosario Vázquez-Larios; Melissa Garibaldi-Rojas; Bernardo Alfonso Martinez-Guerra; Christian Daniel Mireles-Davalos; Samuel Pavel Escalante-Armenta; José Manuel Feliciano-Guzmán; Daniel Romero-Romero; Maria del Consuelo Velazquez-Acosta; Sandra Quintana-Ponce; Shaúl Ariel Navarro-Lara; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2026)
Purpose Systematic collection and analysis of antimicrobial resistance data from key bacterial pathogens is essential to contribute to control antimicrobial resistance (AMR). The aim of this work was to survey the drug resistance on clinically relevant organisms stratified according to age, gender, clinical specimens and facilities. Methods Microbiological data were collected from 55 centers across 24 states in Mexico between January 1 and March 31, 2025. Bacterial identification and antimicrobial susceptibility testing were performed at each participating center using locally available methods. Data was processed using WHONET 2025. Isolates obtained from lower respiratory specimens, urine, blood, biopsies and abscesses were analyzed. Carbapenem non-susceptible isolates were further analyzed by PCR for common carbapenemase-encoding genes. Resistance frequencies were compared using the chi-square test. Results A total of 11,290 clinical isolates were analyzed, mostly from urine ( n = 7,149; 63.3%), followed by blood ( n = 1,370; 12.1%). The most prevalent was Escherichia coli ( n = 6,185; 54.8%), followed by Klebsiella pneumoniae ( n = 1,365; 12.1%) and Pseudomonas aeruginosa ( n = 1,110; 9.8%). Resistance to carbapenems in E. coli was higher in respiratory isolates (imipenem: 5.8%, p = 0.016; meropenem: 5.3%, p < 0.001), with 75.9% producing extended-spectrum ß-lactamases (ESBLs). K. pneumoniae had the highest resistance to ampicillin/sulbactam (52.5%, p = 0.028) and sulfamethoxazole/trimethoprim (62.1%, p = 0.014) in blood isolates, and 63.2% were ESBL-producers ( p = 0.001). In P. aeruginosa , urine isolates showed significantly higher resistance to ceftolozane-tazobactam (24.7%, p = 0.008), ceftazidime-avibactam (36.6%, p < 0.001), and meropenem (34.5%, p = 0.009) compared to other clinical specimens included. For A. baumannii , respiratory isolates had 73.6% resistance to meropenem ( p < 0.001). S. aureus from blood showed 25.7% resistance to oxacillin ( p < 0.004). The most frequent carbapenemase genes were bla OXA−48−like in E. coli (26/56, 46.4%), bla NDM for K. pneumoniae (7/17, 41.2%), bla OXA−24 in A. baumannii (79/108, 73.1%) and bla IMP for P. aeruginosa (18/108, 16.7%). Conclusion This surveillance study underscores the elevated levels of antimicrobial resistance, ESBL production, and carbapenemase activity among priority pathogens, including some Enterobacterales , P. aeruginosa , and A. baumannii . These findings emphasize the urgent need to strengthen epidemiologic surveillance programs in Mexican healthcare settings.

Vascular Endothelial Growth Factor-A and Collateral Circulation in Patients with Acute Ischemic Stroke due to Intracranial Large Vessel Occlusion - Ana Aguilera-Simón; Marina Guasch-Jiménez; Francisco Moniche; Núria Puig; Blanca Pardo-Galiana; Sònia Benítez; Maria del Mar Freijo; Rebeca Marín; Alain Luna; Cristina Gallego-Fabrega; Isabel Fernández-Pérez; Garbiñe Ezcurra-Díaz; et al. (Translational Stroke Research, 2026)

Virtual representation of fresh produce washing in 4.0 industry: Modelling and calibration through optimal experimental design - Ari S. Moreno-Razo; Nerea Martínez-López; Carlos Vilas; Juan A. Tudela; Maria Isabel Gil; Míriam R. García (Innovative Food Science & Emerging Technologies, 2026)

Validation of pharmacokinetic model for quizartinib quantified by UPLC-MS/MS in patients with FLT3-ITD negative newly diagnosed acute myeloid leukemia - Antonio Solana-Altabella; Carles Iniesta-Navalón; Maria Chovi-Trull; Rebeca Rodriguez-Veiga; Marina Lopez-Nogueroles; David Martínez-Cuadrón; Mayte Gil-Candel; Laura Torres-Miñana; Evelyn Acuña-Cruz; Isabel Cano-Ferri; Blanca Boluda; Irene Navarro-Vicente; et al. (European Journal of Clinical Pharmacology, 2025)
Purpose Quizartinib pharmacokinetics in FLT3-ITD negative acute myeloid leukemia (AML) remain largely unexplored. This study aims to validate a population pharmacokinetics model (popPK) for quizartinib in plasma samples of FLT3-ITD negative AML patients. To do so, an ultra-performance liquid chromatography coupled with tandem mass spectrometry (UPLC-MS/MS) method has been developed and validated for the quantification of quizartinib. Methods Plasma samples were collected from FLT3-ITD negative newly diagnosed AML patients undergoing quizartinib therapy at induction in the QUIWI phase II clinical trial [NCT04107727, PETHEMA group] between March 2020 and February 2022. The UPLC-MS/MS method was developed and validated. A previously described popPK model was validated using external validation techniques and implemented using the software NONMEM v7.5. Results The developed UPLC-MS/MS method demonstrated high accuracy and precision with a linear range of 6 to 200 ng/mL, with relative standard deviation between 3–11 and accuracy of 88–97% from nominal values. The external validation of the quizartinib popPK model showed minimal bias at the population level (MdPE: -9.86%; ME: 0.50 ng/mL, p = 0.964), but moderate imprecision (MdAPE: 32.28%) and suboptimal accuracy (F20: 24.5%; F30: 43.4%). Individual predictions improved performance, with negligible bias (MdPE: -0.50%), acceptable precision (MdAPE: 11.27%), and F20 (64.2%) and F30 (77.4%) exceeding predefined thresholds. Visual predictive checks confirmed adequate prediction of median concentrations, though some deviations occurred at extremes. Conclusion This study presents a replicable UPLC-MS/MS method for the determination of quizartinib in plasma. The validated popPK model can be used to optimize dosing strategies in future clinical studies.

First case of triple resistance to EPSPS, ALS, and synthetic auxin herbicides in Bassia scoparia (L.) Voss in Europe - Germán Mora; Miriam Gil-Monreal; Maria Dolores Osuna; Vijaya Bhaskar Alwarnaidu Vijayarajan; José María Montull; Josep María Llenes; Jordi Recasens; Alicia Cirujeda; Ana Isabel Marí; Joel Torra (Pesticide Biochemistry and Physiology, 2025)

Glycogen Synthase Kinase-3β Inhibitor VP3.15 Ameliorates Neurogenesis, Neuronal Loss and Cognitive Impairment in a Model of Germinal Matrix-intraventricular Hemorrhage of the Preterm Newborn - Isabel Atienza-Navarro; Angel del Marco; Pilar Alves-Martinez; Maria de los Angeles Garcia-Perez; Alvaro Raya-Marin; Isabel Benavente-Fernandez; Carmen Gil; Ana Martinez; Simon Lubian-Lopez; Monica Garcia-Alloza (Translational Stroke Research, 2025)
Advances in neonatology have significantly reduced mortality rates due to prematurity. However, complications of prematurity have barely changed in recent decades. Germinal matrix-intraventricular hemorrhage (GM-IVH) is one of the most severe complications of prematurity, and these children are prone to suffer short- and long-term sequelae, including cerebral palsy, cognitive and motor impairments, or neuropsychiatric disorders. Nevertheless, GM-IVH has no successful treatment. VP3.15 is a small, heterocyclic molecule of the 5-imino-1,2,4-thiadiazole family with a dual action as a phosphodiesterase 7 and glycogen synthase kinase-3β (GSK-3β) inhibitor. VP3.15 reduces neuroinflammation and neuronal loss in other neurodegenerative disorders and might ameliorate complications associated with GM-IVH. We administered VP3.15 to a mouse model of GM-IVH. VP3.15 reduces the presence of hemorrhages and microglia in the short (P14) and long (P110) term. It ameliorates brain atrophy and ventricle enlargement while limiting tau hyperphosphorylation and neuronal and myelin basic protein loss. VP3.15 also improves proliferation and neurogenesis as well as cognition after the insult. Interestingly, plasma gelsolin levels, a feasible biomarker of brain damage, improved after VP3.15 treatment. Altogether, our data support the beneficial effects of VP3.15 in GM-IVH by ameliorating brain neuroinflammatory, vascular and white matter damage, ultimately improving cognitive impairment associated with GM-IVH.

Human intestinal enteroids and predictive models validate the operational limits of sanitizers used for viral disinfection of vegetable process wash water - Ana Allende; José Antonio Férez-Rubio; Juan Antonio Tudela; Rosa Aznar; Maria Isabel Gil; Gloria Sánchez; Walter Randazzo (International Journal of Food Microbiology, 2024)

Environmental monitoring of three fresh-cut processing facilities reveals harborage sites for Listeria monocytogenes - Maria Isabel Gil; Pilar Truchado; Juan Antonio Tudela; Ana Allende (Food Control, 2024)

Trophic ecology of common bottlenose dolphins in a pelagic insular environment inferred by stable isotopes - Ester Dias; Morgane Dromby; Rita Ferreira; Ágatha Gil; Raquel Tejerina; L. Filipe C. Castro; Massimiliano Rosso; Isabel Sousa-Pinto; Joel C. Hoffman; Maria A. Teodósio; Ana Dinis; Filipe Alves (Hydrobiologia, 2023)
The common bottlenose dolphin ( Tursiops truncatus ) is a top marine predator widely dispersed in coastal and pelagic habitats and with a generalist feeding behavior. Yet, information on the trophic ecology of animals inhabiting pelagic environments is still scarce. Using carbon (δ 13 C: 13 C/ 12 C) and nitrogen (δ 15 N: 15 N/ 14 N) stable isotope ratios, we identified and quantified the main groups of prey assimilated by bottlenose dolphins inhabiting an oceanic habitat (Madeira Island, East Atlantic). Bottlenose dolphins assimilated pelagic, schooling fish (such as blue jack mackerel, Trachurus picturatus ) and mesopelagic and demersal squids, which reinforces the pelagic dietary composition of insular/oceanic dolphins. Also, intra-seasonal differences were found in their stable isotope ratios, which suggest intraspecific variability in the feeding behavior among individuals living in the same area. Sex was not the main factor contributing to these differences, suggesting the lack of trophic niche segregation between adult males and females in this offshore environment. Nonetheless, further studies including different life stages and information on the ecophysiological requirements are necessary to disclose the factors responsible for the observed variability. This study showed that insular dolphins fed primarily on economically important pelagic prey, highlighting the need of developing management strategies that integrate conservation in fisheries plans.

Antiviral capacity of sanitizers against infectious viruses in process water from the produce industry under batch and continuous conditions - Irene Falcó; Juan A. Tudela; Natalia Hernández; Alba Pérez-Cataluña; Míriam R. García; Pilar Truchado; Agustín Garrido; Ana Allende; Gloria Sánchez; Maria Isabel Gil (Food Control, 2023)

Natural Radionuclides, Rare Earths and Heavy Metals Transferred to the Wild Vegetation Covering a Phosphogypsum Stockpile at Barreiro, Portugal - José Alberto Gil Corisco; Jan Mihalík; Maria José Madruga; Maria Isabel Prudêncio; Rosa Marques; Marta Santos; Mário Reis (Water, Air, & Soil Pollution, 2017)

Cellular and molecular analyses of coffee resistance to Hemileia vastatrix and nonhost resistance to Uromyces vignae in the resistance-donor genotype HDT832/2 - Inês Diniz; Pedro Talhinhas; Helena Gil Azinheira; Vítor Várzea; Clara Medeira; Isabel Maia; Anne-Sophie Petitot; Michel Nicole; Diana Fernandez; Maria do Céu Silva (European Journal of Plant Pathology, 2012)

A comparative study of the pharmacokinetics of ibuprofen arginate versus dexibuprofen in healthy volunteers - Belén Sádaba; Miguel A. Campanero; Maria Jose Muñoz-Juarez; Isabel Gil-Aldea; Emilio García-Quetglas; Antonio Esteras; Jose R. Azanza (European Journal of Clinical Pharmacology, 2006)